2022
DOI: 10.7759/cureus.27500
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment of Haglund’s Deformity: A Systematic Review and Meta-Analysis

Abstract: Posterosuperior calcaneal prominence, also known as Haglund's deformity, can often lead to retrocalcaneal bursitis, a significant cause of posterior heel pain. Surgery is indicated for symptomatic patients, after a period of conservative treatment including analgesia, physiotherapy, activity, and shoe wear modification has failed. Surgical options include both open and endoscopic techniques, and typically involve excision of the retrocalcaneal bursa, resection of the calcaneal prominence, and debridement of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 25 publications
(191 reference statements)
1
10
0
Order By: Relevance
“…Good clinical outcomes after endoscopic calcaneoplasty have been previously described by various studies, 2 , 10 and these outcomes were also recently shown by Yuen et al. 6 to be comparable to outcomes after open surgery.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Good clinical outcomes after endoscopic calcaneoplasty have been previously described by various studies, 2 , 10 and these outcomes were also recently shown by Yuen et al. 6 to be comparable to outcomes after open surgery.…”
Section: Discussionsupporting
confidence: 55%
“… 2 , 3 Endoscopic surgery offers advantages of less operating time and reduced postoperative complications such as Achilles tendon avulsion, surgical wound issues, and postoperative stiffness and pain 4 , 5 while attaining equally good outcomes as open surgery. 6 Techniques for endoscopic calcaneoplasty have been described with variations in portals used and patient positioning. 7 , 8 , 9 …”
mentioning
confidence: 99%
“…Conservative treatments such as training modification (eccentric exercise), extra-corporeal shock wave therapy (ESWT), nonsteroidal anti-inflammatory medication (NSAIDs), and electrotherapy (microcurrent and microwave), are the first choices for patients with Haglund's syndrome (13)(14)(15)(16). Surgery is recommended when conservative treatment has been ineffective after at least 6 months (4,17,18).…”
Section: Discussionmentioning
confidence: 99%
“…17 Overall complications range from 0% to 53%. In the Yuen et al's 18 systematic review, the overall complication rate was 12.3%. The most common complications reported in the literature were paresthesias and incisional numbness.…”
Section: Complicationsmentioning
confidence: 99%